Vapor-assisted crystallization of in situ glycine-modified UiO-66 with enhanced CO2 adsorption. (5th January 2022) - Fujimoto, Yugo; Shu, Yasuhiro; Taniguchi, Yurika; Miyake, Koji; Uchida, Yoshiaki; Tanaka, Shunsuke; Nishiyama, Norikazu
Abstract : Vapor consisting of DMF and HCl promotes crystallization of in situ glycine-modified UiO-66. Abstract : UiO-66, composed of a Zr6 O4 (OH)4 cluster and 1, 4-benzene dicarboxylate, is a promising material for practical chemical processes because it is known as one of the most thermally and chemically stable Metal Organic Frameworks (MOFs). Recently, the structure and composition of UiO-66 have been modified in various ways to improve its functionality and expand its utilization. Herein, we report the synthesis of in situ glycine-modified UiO-66 using a vapor-assisted crystallization (VAC) method. The VAC method using HCl turned out to be the most suitable for synthesizing of glycine-modified UiO-66 with high crystallinity and porosity. Modifying glycine enhanced the CO2 adsorption capacity. In XPS measurement on Zr 3d, the peak shift to higher binding energy was observed by modifying glycine. This result implys that carboxylates derived from glycine chemically interacted with defects of Zr clusters. This work provides a new direction to modify UiO-66.